Analisis Kinerja IFRSUD Zainal Umar Sidiki Gorontalo Ditinjau Dari Perspektif Bisnis Internal Dan Pelanggan - Nurchamidin Gobel; R. A. Oetari; Sa tibi (Jurnal Farmasi Indonesia, 2025)
It is critical to conduct a performance analysis of a hospital's Pharmacy Installation in terms of internal business processes and customer needs. The lack of drugs, delays in medicine stock turnover, unpredictable phases, and the hospital's rank dropping to the lower tier all played a role in this performance. This research aimed to analyze the Pharmacy Installation Performance of the Zainal Umar Sidiki North Gorontalo Regional Public Hospital from an internal business perspective, from a customer perspective, and to provide suggestions for improvements to the Pharmacy Installation Performance of the Zainal Umar Sidiki North Gorontalo Regional Public Hospital using Balanced Scorecard from an internal business perspective and a customer perspective. This research also employs a descriptive method with retrospective and concurrent data collection. Moreover, the study collected data in the form of primary and secondary data. This research was conducted from the second week of December 2020 and ended at the end of February 2021, which lasted approximately two months. The number of samples collected reached 100 people/patients with specific information (outpatients totaling 22 people and inpatients totaling 78 people). The primary data analysis uses descriptive statistical analysis and Microsoft Excel, whereas the calculation of secondary data analysis employs manual calculations. The internal business perspectives that met the standard are those dispensing time indicators, while those that did not meet standards are indicators of drug availability, formulary compliance, percentage of deadstock, damaged ED, final stock value, suitability of planning realization, and drug use review. Customer's (patients) viewpoints that meet the qualified standards are the indicators of customer (patients) satisfaction, while indicators of the level of patient networkability and customer growth do not meet the standard.